SWI Sequence -as a Promising Tool in the Evaluation and Treatment of Acute Stroke - Nishitha, Konduru; Sravan Krishna Reddy A; Prasanna Vaibhav T; Reddy, Bonamukkala Bharath (Asian Journal of Medical Radiological Research, 2022)
Background: There are many recent advances in the magnetic resonance imaging technique that have improved the assessment and evaluation of acute stroke. The susceptibility of tissue is based on its components like hemosiderin, calcium, deoxygenated blood, and ferritin (1). Thrombosed vessels, old hemorrhages, and even tiny minute hemorrhages can easily be detected in SWI sequence. The aim of this study is to depict the importance of SWI sequence in detecting the tissue susceptibility differences which ultimately helps in the assessment and management of both ischemic and hemorrhagic strokes. Subjects and Methods: This hospital-based prospective study was conducted upon 150 patients, over two years from July 2019 to August 2021 at the department of Radio-Diagnosis, Narayana Medical College. The patients who came with complaints of weakness of limbs, headache, vomiting, deviation of the mouth, etc, were subjected to MRI brain study including SWI sequence. Results: Among the 150 studied population, 138(92%) cases had findings and 12(8%) cases are normal. In 138 cases, 99 (71.7%) cases had ischemic infarction, 30 (21.7%) cases had an intraparenchymal hemorrhage and 9(6.6%) cases had venous sinus thrombosis. In 99 cases of ischemic infarction, 38 (38.3%) cases had no hemorrhagic transformation, 35 (35.3%) cases had shown susceptibility sign and 26(26.4%) cases had an early hemorrhagic transformation. Conclusion: Detection of early hemorrhagic transformation within acute infarcts is necessary to prevent the patient from the catastrophic condition due to thrombolytic treatment (2). As SWI sequence detects the early hemorrhagic transformation, it plays a crucial role in planning the management of the patient. It also detects the cause of infarct by detecting the susceptibility sign. Therefore, it is necessary to include the SWI sequence in the routine MRI brain stroke protocol for assessing the patients presented with complaints of stroke.